1984
DOI: 10.1071/ea9840386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of row spacing and plant population on sweet sorghum yield

Abstract: Sweet sorghum (Sorghum bicolor) was grown in an irrigated field trial at Richmond, New South Wales, to determine the effects of row spacing (30, 75, and 105 cm) and plant population (8 and 16 plants/m2) on yields of water soluble carbohydrate (WSC) and dry matter. For both plant populations, narrow row spacing resulted in significantly greater dry matter and WSC yield, especially at seed maturity. Total dry matter and WSC yield also increased with increased plant population from 8 to 16 plants/m2. Much of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…They observed dry biomass yields from 28 to 33 t ha −1 , which would be similar to our yields if converted to dry weight basis. The findings in our row spacing study were similar to what other researchers have observed (Broadhead and Freeman, 1979; Martin and Kelleher, 1984). Broadhead and Freeman (1979) noted that rows spaced at 52.5 cm resulted in higher yields of gross and stripped stalks, and sugar per hectare than 105 cm rows.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…They observed dry biomass yields from 28 to 33 t ha −1 , which would be similar to our yields if converted to dry weight basis. The findings in our row spacing study were similar to what other researchers have observed (Broadhead and Freeman, 1979; Martin and Kelleher, 1984). Broadhead and Freeman (1979) noted that rows spaced at 52.5 cm resulted in higher yields of gross and stripped stalks, and sugar per hectare than 105 cm rows.…”
Section: Resultssupporting
confidence: 93%
“…Also, Jones and Johnson (1991) in the High Plains of Texas observed that increasing row spacing to >76 cm decreased biomass production, leaf area index (LAI), and grain yield. The relatively small amount of row spacing research that has been conducted on sweet sorghum suggests narrower row spacing should increase biomass yield (Broadhead and Freeman, 1979; Martin and Kelleher, 1984). In Mississippi, Broadhead and Freeman (1979) noted that rows spaced at 52.5 cm resulted in higher yields of gross and stripped stalks, and sugar per hectare than 105 cm rows.…”
mentioning
confidence: 99%
“…Data from a series of experiments conducted in the USA suggest that the use of narrow row spacing can increase sweet sorghum yields (from 25% to 50%) (Kresovich and Lawhon, 1981). Moreover, in East Australia Martin and Kelleher (1984) indicated that narrow row spacing at 30 cm gave higher sweet sorghum yields compared to 75 cm and 105 cm. Nevertheless, the determination of the optimum row spacing requires taking into account the productive potential of the location (Godsey et al, 2012;Habyarimana et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…For example, sweet sorghum processors prefer thick stalks that mimic sugarcane; however, higher yield is typically associated with higher plant densities [51]. Furthermore, row spacing modifications are limited to those that fit within existing harvesting equipment.…”
Section: Establishmentmentioning
confidence: 99%